ANTIMICROBIAL RESISTANCE: REVIEW - R. Moutafchieva; D. Mladenov (Trakia Journal of Sciences)
The global increase in antibiotic resistance is a significant challenge in the fields of medicine and microbial ecology. Increasing clinical incidents are a threat to animal and human health, as well as for the protection of the environment. Nowadays the antibiotic resistance grows. The increasing prevalence of it is a serious challenge for both human and animal health. Antibiotic resistance can impose serious constraints on the treatment of many bacterial infections. To avoid its development is necessary to identify the causes and eliminate them. On the first place, the indiscriminate use of antimicrobials should be avoided. That means to know and follow the principles of rational therapy. To prevent the spread of resistance it is necessary to keep strong monitor for the use of antibiotics.